Chapter 17. Sweet Corn Production - Katia Viana Xavier; Ramdas Kanissery; Craig Frey; Anna Meszaros; Nicholas Dufault; Johan Desaeger; Jawwad Qureshi; Julien Beuzelin (EDIS)
Chapter 17 of the Vegetable Production Handbook of Florida